MEDULLARY CONGESTION IN OVARY OF TOPICALLY APPLIED PARAPHENYLENE DIAMINE EFFECTED RAT - Malik, Sana; Noor, Umbreen; Baqar, Ayesha; Qamar, Khadija (Pakistan Armed Forces Medical Journal, 2019)
Objective:To evaluate the effect of topically applied paraphenylene diamine (PPD) on medulla of ovary in Sprague dawley rat.Study Design: Laboratory based randomized control trial.Place and Duration of Study: The study was carried out in the Anatomy Department, Army Medical College, Rawalpindi; in collaboration with animal house, National Institute of Health, Islamabad. The study duration was one year, from Jan 2016 to Dec 2016.Material and Methods:Forty adult Sprague Dawley female rats, weighing 200-300 grams, were used and divided into 4 groups with 10 rats in each group. Group A served as control group and animals were applied with distilled water on dorsal surface clipped free of hair. Group B, C and D were painted with 1mg, 2mg and 3mg per kg body weight of paraphenylene diamine in addition to distilled water on dorsal surface clipped free of hair. The solution was applied for 30 minutes daily for a continued duration of 60 days. All animals were sacrificed on day 60 and right ovary of each rat was removed, fixed in 10% formalin, processed and sectioned. For histological study haematoxylin and eosin (H&E) stains were used. Results:On microscopic examination it was observed that topically applied paraphenylene diamine solution caused vascular congestion in the medulla of ovary.Conclusion:It was concluded from results that topically applied paraphenylene diamine solution induces medullary congestion in ovary of rat.